A Preliminary Three-Dimensional Analysis of Nasal Aesthetics Following Le Fort I Advancement in Patients With Cleft Lip and Palate. Issue 7 (October 2015) - Davidson, Edward; Kumar, Anand R.
Abstract : Abstract: Nasal aesthetic changes after cleft orthognathic surgery remain understudied. Previous scarring associated with prior cleft surgery may affect the predictability of outcomes after jaw surgery. This study evaluates changes in nasal aesthetics using three-dimensional photography after Le Fort I advancement in patients with nonsyndromic cleft-related maxillary hypoplasia. Cephalometric parameters were recorded pre- and postoperatively. Three-dimensional photogrammetric imaging analyzed changes in interalar width (IAW), internostril width (INW), nasal tip projection (NTP), collumelar length (CL), nasal labial angle (NLA), and nasal length (NL). Statistical significance between pre- and postoperative data was determined using T -tests for each parameter. Eleven patients underwent either single piece Le Fort I osteotomy and advancement, (3 bilateral, 4 unilateral cleft lip, and palate), or 2-piece advancement (2 bilateral, 2 unilateral). Average nasal soft tissue changes were IAW 1.9 mm (0.4–4.2), INW −0.2 mm (−2.8 to 1.6), NTP −1.0 mm (−4.0 to 2.0), CL −0.7 mm (−2.9 to 1.5), NLA −0.2° (−13.9 to 15.1), and NL −0.7 mm (−4.3 to 1.5), ( P = 0.001, 0.6, 0.08, 0.01, 0.9, 0.2). For single-piece osteotomy alone changes were IAW 2.1 mm (0.6–4.1), INW −0.6 mm (−2.8 to 1.7), NTP −1.9 mm (−4.0 to 0.3), CL −1.2 mm (−2.9 to 0.03), NLA −1.3° (−13.9 to 15.0), and NL −1.1 mm (−4.3 to 0.7), ( P = 0.007, 0.3, 0.009, 0.0002, 0.7, 0.2). For 2-piece osteotomy alone changes were IAW 1.6 mm (−0.4 to 3.3), INW 0.5 mm (0.4–1.6), NTP 0.5 mm (−1.1–2.0), CL 0.2 mm (−1.4 to 1.5), NLA 2.8° (−7.6 to 10.1), and NL −0.1 mm (−1.4 to 1.5), ( P = 0.2, 0.4, 0.5, 0.6, 0.5, 0.9). Cleft-related scarring and malposition affect changes in nasal aesthetics following maxillary advancement that are different to the noncleft population. Two-piece Le Fort I increases variability of changes in nasal aesthetics compared with single-piece advancement.